2014
DOI: 10.1002/nau.22651
|View full text |Cite
|
Sign up to set email alerts
|

Specific behavioral comorbidity in a large sample of children with functional incontinence: Report of 1,001 cases

Abstract: Children with incontinence have high rates of comorbid behavioral symptoms-three to six times higher than norms. Especially children with FI and combined subtypes of incontinence were affected. As behavioral symptoms and disorders will interfere with incontinence treatment, a general screening is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
3
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 22 publications
1
31
3
4
Order By: Relevance
“…The association between LUTD in children and anxiety and depression is well defined. The latter conditions were found in 29% of children with LUTD vs 6% in healthy controls . Anxiety and depressive disorders rise continuously through childhood from the age of 3 years (earliest age for a diagnosis of depression) and peak in adolescence .…”
Section: Transition Of Childhood DV Into Adulthoodmentioning
confidence: 98%
See 1 more Smart Citation
“…The association between LUTD in children and anxiety and depression is well defined. The latter conditions were found in 29% of children with LUTD vs 6% in healthy controls . Anxiety and depressive disorders rise continuously through childhood from the age of 3 years (earliest age for a diagnosis of depression) and peak in adolescence .…”
Section: Transition Of Childhood DV Into Adulthoodmentioning
confidence: 98%
“…Each of these conditions can be accompanied by UI (Figure ). Behavioral problems are only slightly increased . In many children, DV can be interpreted as an acquired, habitual behavior.…”
Section: Definition Prevalence and Etiology Of DV In Children And Amentioning
confidence: 99%
“…16 The rates of psychiatric comorbidity in a group of 1001 children with bladder and bowel dysfunction were up to six times higher than the rates seen in the general population -43% had clinical-range scores in the CBCL, 36% with externalizing problems and 33% with internalizing problems. 17 The same author described higher rates of symptoms of oppositional defiant disorder (ODD) in children with incontinence than in healthy controls (19.5% vs. 5.2%). 18 In addition to the elevated prevalence of mental disorders in the population with LUTD, the occurrence of the phenomenon varied depending on the type of Another study found that children with MNE had a 2.5-fold chance of presenting emotional disorders than controls.…”
Section: Enuresismentioning
confidence: 99%
“…26 Children with NMNE had even higher scores for behavioral problems when compared to a group of individuals with MNE. 17,26 A prospective study enrolling more than 8,000 children, The Avon Longitudinal Study of Parents and Children (ALSPAC) by Joinson et al, 27 reported a positive association between difficult temperament and behavioral problems in early childhood and occurrence of enuresis in school years.…”
Section: Enuresismentioning
confidence: 99%
“…Paediatricians believe that psychological problems are secondary and are a result of social incapacitation in children with faecal incontinence. Frustration and shame due to the inability to control defecation and occasional incontinence lead to comorbid psychological disorders in these children, which can be improved after successful treatment (25).…”
Section: Suggested Terminology Definitionmentioning
confidence: 99%